The Politics of Marketing the Labour Party - Wring, D. author. aut Link
XII, 262 p.
Keywords: The Labour Party has been using marketing longer than is commonly realised. Leading figures like Morrison, Snowden, Webb, Gaitskell, Benn and Wilson were among those who recognized the importance of imagery and symbolic communication long before the time of Kinnock, Mandelson and Blair. Politics of Marketing the Labour Party traces how the party's political campaigning has developed since its birth and how the increasing use of marketing contributed to the radical restructuring of both the organization and its policies.